Facile synthesis of porous DNA/Protein hydrogels for water purification. (December 2022) - Zhu, Lishan; Wang, Haiqing; Liu, Chao; Xu, Chanchan; Liang, Zhenda; Martyniuk, Christopher J.; Wang, Xiaohong; Zhou, Li; Yan, Bing
Abstract: Porous structured DNA hydrogels with a rapid mass transfer rate constitutes new promising materials for biomedical and environmental applications. However, their biocompatibility can be influenced by the components used to support the structure formation. Here we describe for the first time the use of natural protein stabilized Pickering emulsion as a template for the preparation of porous DNA gel. The results indicated that protein properties including isoelectric point (pI) and size had a great influence on the structure of the DNA gel. Moreover, using bovine serum albumin (BSA) as an example, the morphology and density of the pores in the gel could be well-tuned by the amounts of added proteins. Both CCK-8 and live/dead staining assay showed that the as-prepared gel was highly biocompatible. Considering the intriguing properties, this study demonstrated that the as-prepared gel can be used to prepare columns for efficiently removing multiple pollutants in water via a facile filtration process based on different retention mechanisms, improving the application potential of DNA gel in environmental science. Graphical Abstract: ga1 Highlights: Facile preparation of biocompatible porous DNA/protein hydrogel was described. Protein properties greatly influenced the structure of the hydrogel. The morphology of the pores in the gel can be well tuned by added protein amount. The gel displayed a high swelling capacity and good biocompatibility. The porous gel can be used as novel type of column for water purification.